Creación de microempresas para la elaboración y comercialización de derivados de panela, café y maní, en la parroquia Capiro del cantón Piñas durante el periodo 2013 - Loayza Valarezo, María Fernanda (2013)
The study shows that there are weaknesses in the financial field to organize microenterprises, this phenomenon derived from the low levels of knowledge in organizational matters and procedures for the acquisition of credits, the results of the research demonstrate the favorable conditions that express the behaviors to incorporate to activity .